Utilization of Green Spinach Juice In Making Rolled Omelet - Indira Meutia Mahrani; Eliska Eliska (Universitas Pahlawan Tuanku Tambusai, 2023)
Dadar roll is one of the traditional Indonesian snacks commonly found in traditional markets. Spinach contains lots of Vitamins A and C and a little Vitamin B. Spinach also contains important mineral salts such as calcium, phosphorus, and iron. The research method used is experimental research with the experimental design carried out is a Complete Randomized Design with 3 treatments. The highest average value is indicated by treatment C in terms of color, aroma, texture, and taste. Treatment C is made from rolled omelet with 100gr green spinach + 550cc water (600cc spinach juice). It can be implied that the best C treatment is preferred by the panelists. With an assessment in terms of color, treatment C is the most preferred sample with a mean value of 4.80. In terms of aroma, treatment C is the most preferred sample with a mean value of 4.56. In terms of texture, treatment C is the most preferred sample with a mean value of 4.24. And in terms of taste, treatment C is the most preferred sample with a mean value of 4.28.